Peran Kemaritiman Dalam Memperkuat Perekonomian Indonesia - Pandjaitan, Manahan Budiarto; Khusaini, K; Aminuddin, M. Faisal; Suwarno, Panji (Nama Jurnal Akmi, 2025)
This study examines the role of Indonesia's maritime sector as a driver of sustainable economy. Indonesia as an archipelagic country has a strategic location. Indonesia plays an important role in global trade and geopolitics through the contribution of the fisheries, maritime transportation, and marine tourism sectors. Improving port infrastructure and optimizing the Indonesian Archipelago Sea Lanes supports logistics efficiency and attracts investment, while implementing the right defense strategy improves maritime security. The method used is a literature study, namely the collection and analysis of information from various written sources systematically. The research process is carried out in four stages: recording findings related to research problems, combining data and theories, comparative analysis between sources, and criticism to generate new ideas. The results of the study show that the synergy between maritime policies, infrastructure improvements, and integrated defense strategies can drive Indonesia's transformation into an inclusive and sustainable global maritime economic center.